Dynamic effect analysis of the coiled tubing-in-riser system considering the operation and environmental parameters - Wang, Wenming; Hao, Yi; Wu, Zhenyu; Fan, Jinchao; Lao, Liyun; Chen, Yingchun (Elsevier, 2020)
The dynamic response of the coiled tubing (CT)-in-riser system is critical to the success of offshore CT operations. The purpose of this work is to investigate the mechanical behavior of the CT and the riser and analyze the influencing factors of the coupled system. This paper builds dynamic models of the micro elements of the CT and the riser, and then a coupled model of the CT-in-riser system is presented considering the excitation of ocean loads and the coupling interaction between the inner pipe and the outer pipe. The dynamic coupled model is solved by the finite element method. A finite element model of the CT-in-riser system is built using the Abaqus/AQUA module. The effect of the operating parameters including the top injection force, the top tension, the platform offset, the annular clearance, and the friction coefficient, and the environmental parameters including the ocean depth, current speed, wave period, and wave height are discussed. The results show that the top tension should be properly controlled; the platform offset and friction coefficients should be reduced; the annular clearance should be appropriately reduced; a low current speed and wave height should be selected for operation; and the wave period and wave height have a little effect on the CT axial force. This research can provide important theoretical support for the offshore CT application.
Keywords: The CT; Riser; Finite element method; Influencing factor; Operating parameters; Environmental parameters